Menopauseal hormonal therapy and the risk of breast cancer in the light of new data - O.О. Yefimenko (Publishing House TRILIST, 2022)
Menopause is a natural and inevitable physiological process of the decline of reproductive function due to a decrease in ovarian function, which every woman has to face after about 45-60 years. During this period of hormonal changes the female body needs support more than ever, because the quality of life of a modern woman directly depends on it. The question of the menopausal hormone therapy (MHT) safety in relation to the risk of breast cancer is a perennial subject of research, studied and debated in the medical literature for more than 20 years. During this time, several different studies on this issue were conducted. In this review we describe previous insights along with recent research using estradiol and natural micronized progesterone in MHT regimens. The body of evidence suggests that modifiable lifestyle factors (such as obesity and alcohol consumption) rather than combined MHT are the real breast cancer risks; combined MHT containing estradiol and micronized progesterone was not associated with an increased risk of breast cancer; when prescribing MHT, micronized progesterone may be a safer progestogen. The clinical significance of the obtained results is also discussed.